Basal Cell Carcinoma: A Series of Cases Optometry Should Not Miss - Howard, Danielle Marie; Curry, Jeffery; Wingard, Michael (Canadian Journal of Optometry, 2022)
Basal cell carcinoma (BCC) is a highly prevalent non-melanoma skin cancer that exhibits potentially lethal behavior when left untreated. With the number of cases rising each year secondary to ultraviolet light exposure, eye care clinicians can expect to encounter many cases of BCC throughout their professional career. Because the lids and periocular adnexa are considered high-risk sun-exposed skin, optometrists are well-positioned to recognize and refer patients for treatment prior to the development of significant cosmetic and life-threatening damage. The following is a presentation of three cases suspicious for BCC in varying facial locations followed by a review of clinical features and appropriate treatment options.